Blood Pressure Increase in Hypertensive Individuals During Resistance Training Protocols With Equated Work to Rest Ratio - Paulo, Anderson Caetano; Forjaz, Claudia L. M.; Mion, Décio; Silva, Giovanio V.; Barros, Silvana; Tricoli, Valmor (Frontiers in Physiology, 2020)
Despite the growing evidence about the benefits of resistance training in hypertension, the large and abrupt rise of systolic blood pressure (SBP) observed during resistance exercise execution brings concern about its safety. However, the manipulation of the resistance training protocol (RTP) organization maintaining the work to rest ratio equated between protocols (W:R-equated) may reduce the SBP increase. Purpose: To compare cardiovascular responses during two W:R-equated RTPs (3x15:88s vs 9x5:22s - sets x reps : rest between sets) performed in exercises for lower and upper limbs. Methods: Twelve medicated hypertensives (48 ± 8 ys) randomly performed two RTPs in the bilateral leg extension (BLE) and unilateral elbow flexion (UEF) exercises at 50% 1RM. Increases of SBP, heart rate (HR) and rate pressure product (RPP) during the exercises were measured by photoplethysmography. Results: In both BLE and UEF exercises, SBP was significantly greater during 3x15:88s than 9x5:22s (peak values: BLE = +84 ± 39 vs +67 ± 20 mm Hg, and UEF = +46 ± 25 vs +37 ± 18 mm Hg, respectively, both p < 0.05). HR and RPP were significantly higher in the 3x15:88s than 9x5:22s in BLE (peak values +45 ± 17 vs +30 ± 8 bpm, and +15559 ± 5570 vs +10483 ± 2614 mm Hg . bpm). Conclusion: In medicated hypertensives, a RTP combining more sets with less repetitions per set and shorter rest intervals between sets (i.e. 9x5:22s) produced a smaller increase in cardiovascular load (SBP, HR and RPP) during its execution than a protocol with fewer longer sets (i.e. 3x15:88s).